ISLAMIC CHARITIES AND DAKWAH MOVEMENTS IN A MUSLIM MINORITY ISLAND: The Experience of Niasan Muslims (JOURNAL OF INDONESIAN ISLAM, 2012)
This paper discusses the roles of Islamic charitable organisations in running dakwah activities on Nias Island. By Showing how Islamic charitable organizations have attempted to create welfare programmes under the dakwah scheme, it investigates whether inclusive attitudes towards beneficiaries with different religious backgrounds have characterised Islamic social activism in ‘non-Islamic’ regions. As a Muslim minority area, post-disaster Nias Island has increasingly become a place where Islamic charitable associations and dakwah movements from outside Nias have attempted to deliver aid as well as to assist the communities, notably the Muslim minority population. As the outer islands and isolated regions have become an arena of contestation for religious missionaries, Muslim preachers to a certain extent should compete with Christian missionaries and indigenous religious groups. By way of a case study, this paper also examines the way in which Islamic charitable associations, negotiate between serving the Muslim community through dakwah, and serving humanity at large through social welfare activities.